Vacuum cleaner robotic car/ Nor Ainun Syafiqah Mohd Sazidin, Muhammad Adib Abd Halim and Muhammad Azri Firdaus Mohd Zulkifli - Mohd Sazidin, Nor Ainun Syafiqah; Abd Halim, Muhammad Adib; Mohd Zulkifli, Muhammad Azri (2018)
The main objective of this project is to improvise the vacuum cleaner to more effective way of cleaning. This project present and illustrate the controlled vacuum system and robotic car that is combining together to be an automatic and autonomously vacuum cleaner robotic car. The project consists of both software and hardware design where the ultrasonic sensor as the input to sense the obstacle, the Arduino UNO is used as the controller to the circuit, and motor driver as the output to move a DC motor of robotic car freely. This motor driver is used to move a DC motor of Robotic Car freely. The vacuum system has been included within the robotic car and got a switch ON/OFF near the vacuum. As a conclusion, this project exactly will give such an easier way to be handle and taking just a little bit of time for house duties.